Low Rate of Methicillin-resistant Coagulase-positive Staphylococcal Colonization of Veterinary Personnel in Hong Kong - Boost, M.V; So, S.Y.C; Perreten, V (Zoonoses and public health, 2011)
Elevated rates of methicillin-resistant Staphylococcus aureus (MRSA) carriage have been reported in veterinary personnel, suggesting an occupational colonization risk. Hong Kong veterinary personnel (n = 150) were sampled for coagulase-positive staphylococci (CPS) nasal colonization. Risk factors for colonization were assessed by questionnaire. Isolates were identified and antibiotic susceptibility determined. All CPS isolates were investigated for mecA carriage, SCCmec type and PVL genes. Two subjects were colonized with methicillin-resistant CPS: one with MRSA (spa type t002 (CC5), SCCmec type II) and one with methicillin-resistant Staphylococcus pseudintermedius (MRSP) (MLST type ST71, SCCmec type II-III). MLST type ST71 S. pseudintermedius strain is the predominant MRSP clone circulating in dogs in Europe and in Hong Kong. The low MR-CPS colonization rate may be associated with low levels of large animal exposure or low rates of MRSA colonization of companion animals in Hong Kong. Colonization with non-aureus CPS, which may cause human infection, must also be considered in veterinary personnel.